Employee characteristics for IT workers in a transition job market. (4th January 2010) - Mawhinney, Charles H.; Fustos, Janos; Haga, Wayne; Marold, Kathryn; Moreno, Abel; Morrell, Joseph; Morris, Gerard; Pence, Norman
The bursting of the dot-com bubble in the early 2000s resulted in a tightening of the belt in most sectors but especially in Information Technology. Two key issues faced by employees and would-be employees were: (1) how to get a job in this tight market? and (2) just as significant, how to keep a job in this market? This paper seeks to determine what set of characteristics is important in hiring new employees, what set of characteristics is important in retaining current employees and how the two sets of characteristics compare.